Central American Regional Programmatic Study for the Energy Sector : General Issues and Options - Sector Overview - World Bank (World Bank, 2012)
The six Central American countries of Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama share a long tradition of regional integration, including a common market, substantial intraregional trade, as well as coordinated commercial policies, such as the Central American Free Trade Agreement (CAFTA) with the US. The most significant example of regional integration in the energy subsector consists of the Sistema de Interconexion Electrica para America Central (SIEPAC), an interconnection line that is expected to link the six countries in mid-2010. The creation of the interconnection has been a long-term effort, starting in the early 1990s and culminating in 2010. This report provides an overview of the energy sector in Central America, with a focus on the power subsector, and highlights the key challenges and options for meeting future energy and development goals. One of the main objectives of the study is to identify paths for collective action whereby individual countries, and the region as a whole, could benefit from a more integrated approach to developing energy infrastructure and connecting energy markets.